Evaluating sawdust-based bioethanol and pyrolysis products in the European Union: Feedstock availability, life cycle assessment, and techno-economic analysis - Ghani, Hafiz Usman; Ilvesniemi, Hannu; Leinonen, Ilkka; Ruuttunen, Kyösti; Khan, Md Musharof Hussain; Oinas, Pekka; Anttila, Perttu (Elsevier, 2025)
The significance of biomass-derived biofuels in global transport is increasing due to their perceived environmental advantages and policies with binding use targets. This study conducted a comprehensive sustainability analysis of sawdust-based bioethanol in the European Union, encompassing evaluations of sawdust availability, techno-economic assessment (TEA), and global warming potential (GWP), including land use and land-use-change-related GWP (GWP-LULUC). It was found that bioethanol production based on average annual sawdust potential could replace only 0.5 % of total fuel consumption in the EU transport sector in 2021, provided that all the sawdust was used for this purpose. The TEA calculations indicated that, while technically feasible, the economics of sawdust-based bioethanol production are not favourable based on this research's assumptions. Pyrolysis-based bioproducts showed better profitability. The economics of bioethanol production depends greatly on the sawdust cost, which was shown by the sensitivity analysis conducted. The GWP results highlighted the potential environmental benefits of ethanol-blended fuels such as E20 (20 % bioethanol with gasoline) and E85 (85 % bioethanol with gasoline), demonstrating reductions of 18 % and 78 % in fossil GWP impacts compared to petrol respectively. Examining GWP-LULUC unveiled a notable sequestration effect, primarily due to increased carbon storage in forests. However, these effects vary depending on the production year, country of origin, or soil type. In the context of this study, sawdust-based bioethanol demonstrated the potential to replace some fossil fuels, offering technical feasibility and considerable environmental benefits. However, it is not economically feasible and is highly influenced by policy changes and competition among different sectors.
Keywords: bioresource; bioethanol; forest; life cycle assessment; techno economic assessment